A Study Of The Traditional Characteristics Of Yemeni Houses In The Port City Of Aden And Mukalla: Perception Of Architects And Students - Binthabet, Aqeil Ahmed (2007)
The research attempts to study the characteristics of traditional houses in the port city area of Aden and Mukalla in Yemen. This involves a study on a perception of arch~ects and students. The study intends to Investigate the respondent's viewpoints, the level of willingness, level of preference and satisfaction in order to provide a description of the houses. arch~ectural criteria, distinctive features and future conceptions for development. In this manner, the true characteristics of the houses In the area could be rediscovered for future reference. The study starts with literature description on the general overview of location, geographical divisions, climate and economy of the port city of Aden and Mukalla. The study describes the house types In Aden and Mukalla, variations In traditional houses in the five distinctive regions in Yemen. traditional houses, the problems and factors affecting the design of traditional housing in Aden and Mukalla. The field survey method has been chosen for this research by preparing questionnaires to identify the architectural identity from the respondents that includes professional architects and architectural students. All the information gathered from the survey are collected and analysed using qual~ative data based on responses of pos~ive and negative answers by the respondents. The result shows that most of the categories have positive answers on the importance of traditional values in house design. This indicates that the future housing development in the port city of Yemen must consider the traditional architectural elements in design. In conclusion. this study proposes 6 design guidelines and recommendation for future housing development in the port city of Aden and Mukalla. This includes design aspects related to the house layout, the application of traditional design, lhe traditional building material, the Islamic values in house design, the exterior appearance of the house and thermal comfort conditions.